Oxygen Electrocatalysis: Topological Defects in Metal‐Free Nanocarbon for Oxygen Electrocatalysis (Adv. Mater. 32/2016). Issue 32 (August 2016) - Tang, Cheng; Wang, Hao‐Fan; Chen, Xiang; Li, Bo‐Quan; Hou, Ting‐Zheng; Zhang, Bingsen; Zhang, Qiang; Titirici, Maria‐Magdalena; Wei, Fei
Abstract : On page 6845, Q. Zhang, M.‐M. Titirici, F. Wei, and co‐workers describe a bifunctional graphene catalyst with abundant topological defects through the facile carbonization of natural gelatinized sticky rice and probe the underlying oxygen electrocatalytic mechanism. A nitrogen‐free configuration with adjacent pentagon and heptagon carbon rings is revealed to exhibit the lowest overpotential for both oxygen reduction and evolution catalysis.